2019
DOI: 10.1016/j.afjem.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and outcomes of paediatric trauma at a tertiary teaching hospital in Kenya

Abstract: Introduction Trauma continues to be a major cause of morbidity and mortality especially in the paediatric population of low- and middle-income countries such as Kenya. The aim of this study was to establish the profile and outcomes of admitted paediatric trauma cases at the Aga Khan University Hospital, Nairobi. Methods This retrospective, descriptive study involved a 12-month chart review (January 2016–December 2016). A total of 218 records were identified of which 144… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
5
9
0
Order By: Relevance
“…In agreement with many previously published studies, our study also shows male predilection for injuries, males 67.9 %( n=595) and females 32.1 %( n=276). 21,22,23 The present study revealed that 3-5 years age group is the most common victim of trauma,39%(n=340). 6-10.9 years 20.7%(n=2038) has been reported as the most frequently injured age group 10 A study conducted in India reported that 11-15 years comprised the most common age group involved in trauma.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In agreement with many previously published studies, our study also shows male predilection for injuries, males 67.9 %( n=595) and females 32.1 %( n=276). 21,22,23 The present study revealed that 3-5 years age group is the most common victim of trauma,39%(n=340). 6-10.9 years 20.7%(n=2038) has been reported as the most frequently injured age group 10 A study conducted in India reported that 11-15 years comprised the most common age group involved in trauma.…”
Section: Discussionsupporting
confidence: 49%
“…This finding was supported by many previously published studies. 19,25,26,27 Unlike the previous studies 21,22,28 fall was not the most common injury mechanism, rather it was the second most common injury mechanism, 34.0 %( n=238). Vehicle related incidents are the most common injury mechanism in boys and fall is most common in girls.…”
Section: Discussionmentioning
confidence: 62%
“…This assertion was also corroborated by others, e.g. Halawa et al [3], Heidenkeni et al [4], Ndung’u et al [5]. Overall assessment of morphological structure of the feet, and any attendant deformities in terms of their impact on postural stability, is therefore believed an essential and challenging research issue in many areas.…”
Section: Introductionsupporting
confidence: 64%
“…This aspect is addressed in four of the papers included in this special issue, ranging from low income to middle income countries. [3] , [5] , [6] , [7] …”
mentioning
confidence: 99%
“…Ndung’u and co-authors examined this aspect in a Kenyan emergency centre attached to Aga Khan University, including children and younger adolescents (under 15 years of age). [6] They noted that paediatric injury was common in the younger child, around 6 years of age, due to domestic incidents and falls, while a smaller number had penetrating trauma. Admissions were predominantly for limb fractures, with only 4% of the total cohort resulting from intentional injury, very different from the adult population.…”
mentioning
confidence: 99%